System allowing adhesion force change of road vehicle - Jilek, Petr; Šefčík, Ivo; Verner, Jan; Berg, Jan (Latvia University of Afgriculture, 2019)
Bringing the car into a skid is realised by the adhesion force decrease. This can be reached either by a coefficient of adhesion decrease or decrease of a radial reaction on the vehicle’s wheel. For the purpose to the vehicle’s behaviour change according to stability we chose the way of radial reaction change. To decrease the adhesion force transferred by the vehicle’s wheels, the required part of radial reaction of a particular vehicle’s wheel was transferred to the road, out of the vehicle’s wheels, using additional auxiliary wheels. The auxiliary wheel units are connected to suspension arms. The article contains individual currently used ways for the adhesion force change and the unique way in the form of the system SlideWheel designed by the authors. The system SlideWheel, which was designed by the authors of this article, consists of three circuits. The first circuit is the mechanical part of the wheel unit, the second one is designed in the form of a hydraulic system and the third circuit is an electrical system used to control the wheel unit’s lift through the hydraulic system. The system was designed to be used for experimental measurement purposes in education in order to experimentally simulate oversteer or understeer of the vehicle. The real measured data from a particular drive test are stated and evaluated in the conclusion. The measurement is implemented on a special experimental vehicle equipped with the SlideWheel system. Based on the experimental measurements, we have come to the conclusion that using the SW system, it is possible to change the adhesion force of a road vehicle.The paper deals with a new system for radial reaction change of vehicle wheels. This system has minimal added weight to the vehicle. At the same time, none of the components exceeds the ground plan of the vehicle. With the newly created system, it is possible to reduce radial reactions on any car wheel. The measured results are consistent with the vehicle’s ride on sliding surfaces.
Systém umožňující změnu adhezní síly u silničního vozidla
Keywords: road vehicle; adhesion; tyres; SlideWheel; silniční vozidlo; adheze; pneumatiky; SlideWheel